Bandgap Engineering of Lead-Halide Perovskite-Type Ferroelectrics - Ye, Heng-Yun; Liao, Wei-Qiang; Hu, Chun-Li; Zhang, Yi; You, Yu-Meng; Mao, Jiang-Gao; Li, Peng-Fei; Xiong, Ren-Gen (Advanced materials (Weinheim), 2016)
Semiconducting ferroelectricity is realized in hybrid perovskite‐type compounds (cyclohexylammonium)2PbBr4−4xI4x (x = 0–1). By adjusting the composition x, the bandgap is successfully tuned from previously reported 3.65 eV to as low as 2.74 eV, and the excellent ferroelectricity was kept intact. This finding may contribute to improving the photoelectronic and/or photovoltaic performance of hybrid perovskite‐type compounds.